Understanding the fatigue response of small volume specimens through novel fatigue test methods – Experimental results and numerical simulation. (October 2019) - Prakash, Raghu V.; Dhaka, Pankaj; Prasad Reddy, G.V.; Sandhya, R.
Highlights: Fatigue responses of materials are evaluated through cyclic ABI and cyclic SPT tests. Stress state is bi-axial (cyclic SPT) or tri-axial (cyclic ABI), different from uni-axial specimen. Mean stress during cyclic loading is different; correlation with strain-life data is difficult. Numerical simulation of cyclic ABI, cyclic SPT and hydraulic bulge test carried out. Mean stress for three test methods is different; can be correlated using Goodman method. Abstract: This paper presents the current understanding relating to fatigue response of materials that are small in volume and tested through cyclic automated ball indentation and cyclic small punch test methods. The paper covers both the experimentation and numerical simulation aspects. Recently, researchers have proposed the hydraulic bulge test as another test method for fatigue life evaluation. All these test methods provide an indication of failure due to fatigue loading. For any given material, each one of the test methods causes its own state of stress (bi-axial or tri-axial), which is different from the uni-axial state of stress for a standard specimen, which makes the correlation of strain-life data between test methods to be difficult. In view of this, a numerical simulation of cyclic ball indentation, cyclic small punch test, and hydraulic bulge test has been carried out. The results of numerical simulation suggest that the mean stress for cyclic ABI and cyclic SPT tests are different, but the failure life data can be corrected using Goodman or similar mean stress correction methods.